2020
DOI: 10.1111/jonm.12937
|View full text |Cite
|
Sign up to set email alerts
|

Association between nursing work environment and compassion satisfaction among clinical nurses

Abstract: Aim This study investigated the association between nursing work environment and compassion satisfaction among clinical nurses. Background Nursing work environment and compassion satisfaction are important factors for preventing burnout and decreasing clinical nurse turnover. Method This study used a secondary analysis and obtained data from a previous cross‐sectional study. Results The mean scores (mean ± SD) for the nursing work environment and compassion satisfaction were 2.54 ± 0.34 and 33.40 ± 6.69, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
6
19
0
Order By: Relevance
“…The present study revealed that the work environment of haemodialysis nurses in Greece is considered marginal healthy, as three out of five work environment items were rated positively. This finding is consistent with those of two other studies where haemodialysis nurses rated their work environments as positive (Baek et al, 2019; Hayes, Douglas, et al, 2015). Improvement in the work environment of nurses is an important tool to ensure both the quality of health services provided and the well‐being of the nursing staff.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study revealed that the work environment of haemodialysis nurses in Greece is considered marginal healthy, as three out of five work environment items were rated positively. This finding is consistent with those of two other studies where haemodialysis nurses rated their work environments as positive (Baek et al, 2019; Hayes, Douglas, et al, 2015). Improvement in the work environment of nurses is an important tool to ensure both the quality of health services provided and the well‐being of the nursing staff.…”
Section: Discussionsupporting
confidence: 92%
“…As for the present study, the participants reported the nurse managers' ability to lead and support, along with collegial nurse–physician relations, as the most positive components of their work environment. Over time, these aspects have received the highest score in haemodialysis units and are associated with the nurses' intention to leave their jobs, their compassion satisfaction and the number of dialysis patients that have been hospitalised (Baek et al, 2019; Gardner et al, 2007; Thomas‐Hawkins, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that strategies such as self-care, collegial support, management support, debrie ng, psychological support and supportive environment are useful strategies in prevention and management of CF (18,19). Moreover, Baek et al, (2020) concluded that creating supportive work environment and improving the organizational support for adequate human resources could be effective ways to prevent CF among nurses (27). In line with this study, Pergol-Metko & Czyżewski stated managers should pay special attention to the number of working hours of nurses because overtime work is an important predictor of CF (28).…”
Section: Discussionsupporting
confidence: 52%
“…Compassion satisfaction, burnout and compassion fatigue is a very important component of ProQOL. High compassion and resillience may relieve compassion fatigue, burnout and turnover rates (Baek et al, 2019). The first step in lowering compassion fatigue and burnout (and thus preventing compassion fatigue) is to recognize the signs and symptoms of compassion fatigue and burnout by nurse mangers.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses working in intensive care units -where bedside care services are provided and where ongoing care and treatment are maintained -face psychosocial stressors resulting from both the environment they work in and the intense working conditions of the clinical area (Amin et al, 2015). Many factors cause nurses to feel stressed, such as time pressure, workload, having many responsibilities, caring for dying patients, and ethical and emotional problems (Baek et al, 2019;Ingebretsen and Sagbakken, 2016;Lim et al, 2011;McCann et al, 2013). The intense stress experienced can negatively impact nurses professionally and mentally and may lead to a condition called compassion fatigue (Craigie et al, 2016;Figley, 1995).…”
Section: Introductionmentioning
confidence: 99%